Geminal dianionic complexes and their corresponding carbenoids for small molecule activation - Ho, Samuel Ying Fu (2016)
The thesis describes the synthesis of metal carbenoids and their application towards small molecule activation and the catalytic reduction of CO2 with borane. Chapter 1 describes the synthesis of a novel unsymmetric phosphonium-stabilized methane ligand, the monoanionic and dianionic lithium and magnesium derivatives. Their electronic structures were elucidated by X-ray crystallography and DFT calculations. Chapter 2 reports the mild oxidation of the dianionic complexes, which underwent an unprecedented intramolecular B-H insertion with BH3 into the central carbon via a carbenoid species. In addition, the carbenoid Ph2P(S)C(Cl)P(S)Ph2Li, underwent a similar intermolecular B-H insertion with BH3. The mechanism of the B-H bond insertion was studied by NMR spectroscopy and DFT calculations, which shows the concerted bond breaking of a B-H and C-Cl bond and the bond forming of a Li-Cl and C-H bond. This accounts for the low energy required for the B-H insertion reaction. Moreover, the attempted isolation of the magnesium carbenoid intermediate was described. The synthesis and reactivity of bis(iminophosphoranyl)carbenoid Ph2P(NMes)C(Cl)P(NMes)Ph2Li (Mes = 1,3,5-Me3C6H2 ) was presented in Chapter 3 and reacted with BH3 yielding the boronium species. ClC(PPh2NMes)2BH2, and LiBH4. Chapter 4 describes the application of the boronium as one of the best catalyst for CO2 reduction by BH3. An intermediate ClC{PPh2NMes}2BH{OC(O)H} was isolated and a mechanism of this transformation was proposed. Lastly, in chapter 5, the step wise synthesis of a novel unsymmetric carbenoid and its reactivity with BH3 was probed and showed a B-H insertion reaction.